2020
DOI: 10.1007/s11135-020-01052-z
|View full text |Cite
|
Sign up to set email alerts
|

Conducting quantitative studies with the participation of political elites: best practices for designing the study and soliciting the participation of political elites

Abstract: Conducting quantitative research (e.g., surveys, a large number of interviews, experiments) with the participation of political elites is typically challenging. Given that a population of political elites is typically small by definition, a particular challenge is obtaining a sufficiently high number of observations and, thus, a certain response rate. This paper focuses on two questions related to this challenge: (1) What are best practices for designing the study? And (2) what are best practices for solicitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The questionnaire included questions about social media. The response rate was 17.2%, which is not high but is also not unusual in social science research regarding political elites (Harden, 2013; Vis and Stolwijk, 2021), and this rate was sufficient for our purpose. The questionnaire was sent to all MEPs in English only.…”
Section: Methodsmentioning
confidence: 90%
“…The questionnaire included questions about social media. The response rate was 17.2%, which is not high but is also not unusual in social science research regarding political elites (Harden, 2013; Vis and Stolwijk, 2021), and this rate was sufficient for our purpose. The questionnaire was sent to all MEPs in English only.…”
Section: Methodsmentioning
confidence: 90%
“…This appears low but is close to that of several recent studies of political elites, who are getting more difficult to reach in the Internet age (cf. Li 2018; Vis and Stolwijk 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In sub-Saharan Africa, MPs are expected to be accessible to their constituents, but the busy nature of their work often makes them less available for engagements outside parliamentary duties ( Stapenhurst et al, 2020 ). This challenge of time constraint has been implicated for the reality that in some contexts, MPs may be a hard-to-reach population for research ( Vis & Stolwijk, 2020 ), while published studies with lower response rates involving MPs are not uncommon ( Alemna & Skouby, 2000 ; Rao et al, 2020 ; Sakyi, 2010 ). Against this backdrop, some studies have (rather) found useful the analysis of Parliamentary Hansards to help gauge MPs’ views and how they frame health issues of national and international importance such as youth mental health ( Whiteford et al, 2016 ), HIV/AIDS and reproductive health ( Muula, 2006 ), malnutrition ( Namugumya et al, 2021 ), and public place restriction on smoking ( Asbridge, 2004 ).…”
Section: Methodsmentioning
confidence: 99%